On the construction of nonequatorial minimal hyperspheres in S(n)(1) with stable cones in R(n+1) - Hsiang, Wu-yi (1984)
Within the framework of equivariant differential geometry, we outline the construction of some imbedded minimal hyperspheres of S(n)(1) and show that many of them have a stable cone in R(n+1). The statement of these and related results are given.